The effect of solution pH on cullet - P2O5 - CaO based glass - 288596 Mazlina Mat Darus; Md. Rahim Sahar, 1957-; Regional Conference on Solid State Science and Technology (17th : 2000 : Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2000)
42